RNA‐PROTACs: Degraders of RNA‐Binding Proteins. Issue 6 (10th December 2020) - Ghidini, Alice; Cléry, Antoine; Halloy, François; Allain, Frédéric H. T.; Hall, Jonathan
Abstract: Defects in the functions of RNA binding proteins (RBPs) are at the origin of many diseases; however, targeting RBPs with conventional drugs has proven difficult. PROTACs are a new class of drugs that mediate selective degradation of a target protein through a cell's ubiquitination machinery. PROTACs comprise a moiety that binds the selected protein, conjugated to a ligand of an E3 ligase. Herein, we introduce RNA‐PROTACs as a new concept in the targeting of RBPs. These chimeric structures employ small RNA mimics as targeting groups that dock the RNA‐binding site of the RBP, whereupon a conjugated E3‐recruiting peptide derived from the HIF‐1α protein directs the RBP for proteasomal degradation. We performed a proof‐of‐concept demonstration with the degradation of two RBPs—a stem cell factor LIN28 and a splicing factor RBFOX1—and showed their use in cancer cell lines. The RNA‐PROTAC approach opens the way to rapid, selective targeting of RBPs in a rational and general fashion. Abstract : RNA‐PROTACs are new chimeric structures that mediate the proteasomal degradation of RNA‐binding proteins (RBP). They comprise an E3‐recruiting peptide conjugated to a short modified RNA, which is iso‐sequential with the native binding element to which the RBP binds in cells. RNA‐PROTACs offer a fast, rational and general approach to target an entire class of protein (RBPs) that has proven difficult until today to target pharmacologically.